An FDTD model of scattering from meteor head plasma. Issue 7 (20th July 2015) - Marshall, R. A.; Close, S.
Abstract: We have developed a three‐dimensional finite difference time domain (FDTD) model of scattering of radar waves from meteor head plasma. The model treats the meteor head plasma as a cold, collisional, and magnetized plasma, and solves Maxwell's equations and the Langevin equation simultaneously and self‐consistently in and around the plasma. We use this model to investigate scattering of radar waves from a meteor head (the "head echo") under a range of plasma densities, meteor scale sizes, and wave frequencies. In this way we relate the radar cross section (RCS) to these variable parameters. We find that computed RCS disagrees with previous analytical theory at certain meteor sizes and densities, in some cases by over an order of magnitude. We find that the calculated meteor head RCS is monotonically related to the "overdense area" of the meteor, defined as the cross‐section area of the part of the meteor where the plasma frequency exceeds the wave frequency. These results provides a physical measure of the meteor size and density that can be inferred from measured RCS values from ground‐based radars. Meteoroid mass can then be inferred from the meteor plasma distribution using established methods. Key Points: Developed 3‐D FDTD model of scattering from meteor head Simulated meteor RCS for range of meteor sizes and densities Found that RCS can be predicted from meteor overdense area